The Effect of the Accuracy of Inpatient Disease Codification on BPJS Health Claims At Hermina Arcamanik Hospital - Awalia*, Rahma Kurnia; Ulfah, Annisa (Universitas Syiah Kuala, 2023)
The accuracy of codification of patient diseases is one of the fundamental things in medical record governance. Discrepancies in the provision of disease codes and actions could have an impact on the health service financing claim process. The goals of this study are to find out about the effect of the accuracy of inpatient disease codification on BPJS Health claims at Hermina Arcamanic Hospital. A descriptive approach in quantitative methods was used in this study with 98 samples of pending RM files. The problem found was data discrepancies in the claim process. Problems related to codification include the occurrence of repeated codification inputs, actions that do not need to be coded, other supporting files that do not meet the claim criteria, the occurrence of action 88.78 recording, and inaccuracies in the selection of Main Condition. The results showed that the difference in tariffs obtained by Hermina Arcamanik Hospital was 55.87 with a negative difference. The efforts to overcome these problems include conducting a thorough check on the disease to be coded and the necessary supporting files, evaluating the performance of the case mix section, and evaluating the number of hospital rates so that there is no too significant cost gap with INA-CBGs rates.